2003
DOI: 10.1046/j.1365-2567.2003.01672.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclosporin A and a rapamycin derivative (SAR943) on chronic allergic inflammation in sensitized rats

Abstract: SUMMARYImmunomodulators such as cyclosporin A (CsA) and SAR943 (32-deoxorapamycin) inhibit single allergen-induced allergic in¯ammation such as eosinophilic and lymphocytic in®ltration and mRNA expression for interleukin (IL)-4 and IL-5. We examined the effects of CsA and SAR943, administered orally, on asthmatic responses in a rat model of chronic allergic in¯amma-tion. Sensitized Brown-Norway (BN) rats were exposed to ovalbumin (OVA) aerosol every third day on six occasions. CsA (5 mg/kg/day), SAR943 (2Á5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…However, another report showed that CsA treatment was associated with down-regulation of IgE production via suppressing the secretion of such Th2 cytokines as IL-4 and IL-5 25 . In our study, the serum level of total IgE was significantly decreased after the CsA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, another report showed that CsA treatment was associated with down-regulation of IgE production via suppressing the secretion of such Th2 cytokines as IL-4 and IL-5 25 . In our study, the serum level of total IgE was significantly decreased after the CsA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although rapamycin exhibited potent antitumor effects in experimental tumor models, it failed to demonstrate promise as an anticancer drug in clinical trials [85–87]. Hence, rapamycin analogues (rapalogues) with more favorable pharmaceutical characteristics such as RAD001 (Everolimus), CCI-779 (Temsirolimus), AP23573 (Deforolimus), SAR943 (32-deoxorapamycin) and ABT-578 (Zotarolimus) have been developed [51, 52, 88, 89]. RAD001 and CCI-779 have been approved by the FDA for the treatment of advanced renal cell carcinoma [53,90].…”
Section: Therapeutic Targeting Of Cap-dependent Translational Complexmentioning
confidence: 99%
“…These second generation (catalytic) mTOR inhibitors can effectively minimize the feedback activation of Akt by mTORC2 to avoid offsetting their effects of sequestering eIF4E. Importantly, they inhibit 4E-BP phosphorylation more strongly than rapamycin and rapalogues [88]. Another potential class of mTOR kinase inhibitors is the dual PI3K/mTOR inhibitors.…”
Section: Therapeutic Targeting Of Cap-dependent Translational Complexmentioning
confidence: 99%
“…In some studies, rapamycin has been suggested to inhibit pathological changes of allergic asthma, including airway hyperresponsiveness (AHR), eosinophilic airway inflammation, goblet cell hyperplasia and IgE production; [7][8][9][10] however, other works have also shown that it has little effects on the allergic airway inflammation and AHR. [11][12][13] Most importantly, the underlying mechanisms that mediated the effects of rapamycin in the process of allergic asthma remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%